Optimal recloser placement for improving distribution system reliability using particle swarm optimization / Nur Afifah Auni Mohd Nasir - Nur Afifah Auni , Mohd Nasir (2017)
Growing energy demand leading to increase attention to adequate reliability and efficient protection of electrical system. Improving the reliability can increase customer satisfaction. System reliability of distribution network improved by installing optimal number and location of protective equipment which is recloser. Since recloser can reduce the number and duration of power outages in the distribution system, this thesis presents optimal recloser placement which can reduce the reliability indices, System Average Interruption Frequency Index (SAIFI) and System Average Interruption Duration Index (SAIDI). The optimization method is solved using Particle Swarm Optimization (PSO) algorithm that has gained much popularity among researchers since after its introduction. The Roy Billinton Test System (RBTS) had been used for studying the impact of optimal recloser placement to the distribution system reliability. In order to investigate the impact of different number of optimal recloser placement, up to six number of recloser are used in this project. From the simulation, PSO has successfully obtained the location of recloser based on minimum value of SAIFI and SAIDI.